The Effects of Land Use Factor on Land Degradation due to Erosion at Primary Forest and Mixed Plantation in The District of Kairatu West Seram Regency, Maluku Province - Silwanus M. Talakua (Faculty of Agriculture, Pattimura University, 2020)
Land use is the most vulnerable factor and has always been the main target for the effects of change by humans compared to other factors, therefore it has the potential for land degradation due to erosion. The research purposes was to analyze the influence of land use factors including land use area, upper vegetation density, lower vegetation density, and the dominant factors that influenced of land degradation due to erosion in primary forest and mixed plantation in Kairatu Sub District, West Seram District, Maluku Province. The method used was the measurement of land degradation indicators in the field (field assessment). The results showed that the area of land use has a significant negative effect on land degradation due to erosion in primary forest (P = 0.040*; r = -0.71), and a significant positive effect (P = 0.003*; r = +0.86) in mixed plantation. The upper vegetation density factor has a significant negative effect in the primary forest (P = 0.006*, and r = -0.82) and in the mixed plantation (P = 0.002*; r = -0.886). The lower vegetation density factor has a significant negative effect both in primary forest (P = 0.020; r = -0.77) and in the mixed plantation (P = 0.000*; r = -0.92. The dominant and most influence factors on land degradation due to erosion in the primary forest land use is the density of upper vegetation (Pparsial X2HP = 0.006*; R2 = 0.68, while in the mixed plantation is the area of land use (Pparsial X1KC / P = 0.004*) and lower vegetation density (Pparsial X3KC / P = 0.042*) with a value of R2 = 0.88.